Fiscal impulse in the Brazilian economy, 1989-1996 - Afonso S. Bevilaqua; Rogério L.F. Werneck (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 1997)
This paper develops an alternative indicator of fiscal policy which allows a more accurate picture of the underlying fiscal trend in the Brazilian economy over the recent period. This indicator corrects conventional fiscal-stance measures for the effects of theeconomic cycle, and yields a measure of the discretionary change in the budgetary position of the public-sector, known as the fiscal impulse. Section 2 briefly examines the evolution of traditional fiscal policy indicators over the recent period, detecting the bottom line of the changes in the fiscal stance. The details of the estimation of the fiscal impulse measure for the Brazilian economy are presented in Section 3. Section 4 concludes the paper with a reassessment of recent fiscal policy episodes, using the data generated in the previous section. The resulting fiscal-impulse measure indicates that, on average, the fiscal stance during 1989-96 was more expansionist than suggested by traditional fiscal policy indicators.
Keywords: 330